2015
DOI: 10.1590/01000683rbcs20150080
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nitrogen in a Typic Hapludox Fertilized With Pig Slurry

Abstract: The application of pig slurry may have a different effect on nitrogen dynamics in soil compared to mineral fertilization. Thus, the aim of this study was to determine the different forms of organic n in a latossolo Vermelho distroférrico (Typic Hapludox) and their relationship to n uptake by crops in response to 10 years of annual application of pig slurry and mineral fertilizer. The treatments were application rates of 0, 25, 50, 100, and 200 m 3 ha -1 of pig slurry, in addition to mineral fertilizer, organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
(27 reference statements)
3
9
2
1
Order By: Relevance
“…The organic fraction of the nutrient corresponds to 95% of the total N present in the soil (Müller et al, 2011). The SOM levels in this study may be classified as medium and high (Silva et al, 2016), which would allow them to stabilize the N content in the soil (Mafra et al, 2014;Grohskopf et al, 2015).…”
Section: Resultsmentioning
confidence: 80%
“…The organic fraction of the nutrient corresponds to 95% of the total N present in the soil (Müller et al, 2011). The SOM levels in this study may be classified as medium and high (Silva et al, 2016), which would allow them to stabilize the N content in the soil (Mafra et al, 2014;Grohskopf et al, 2015).…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, research is needed on reuse of the nutrients available in organic waste (Grohskopf et al, 2015) and the use of highly productive conservation systems, such as integrated crop-livestock production systems (ICL), which place particular importance on soil fertility (Tormena et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The total nitrogen at 0.30 m depth presented a quadratic behavior with maximum concentrations of 1.85 g kg -1 in the ALT4 treatment submitted to 600 kg ha -1 of N ( Figure 4A) and quadratic ( Figure 4B), with a maximum concentration of 1.06 g kg -1 in the AAT3 treatment submitted to the dose of 450 kg ha -1 of N. Grohskopf et al (2015) found total nitrogen concentrations at 0.10 m depth of 2.70 g kg -1 when received the 200 m 3 ha -1 of swine wastewater (SW).…”
Section: Resultsmentioning
confidence: 94%